Analysis of radio astronomy bands using CALLISTO spectrometer at Malaysia-UKM station - Zavvari, A.; Islam, M.T.; Anwar, R.; Abidin, Z.Z.; Asillam, M.F.; Monstein, C. (Kluwer (now part of Springer), 2016)
The e-CALLISTO system is a worldwide network that aims to observe solar radio emission for astronomical science. CALLISTO instruments have been deployed worldwide in various locations that together can provide continuous observation of the solar radio spectrum for 24 h per day year-round. Malaysia-UKM is a strategic equatorial location and can observe the Sun 12 h per day. This paper gives an overview of the spectrum allocation for radio astronomy, which falls in the specified operating frequency band of the CALLISTO spectrometer. The radio astronomy bands are analyzed at the Malaysia-UKM station according to the International Telecommunication Union recommendations. Some observational results are also presented in this paper.